A museum studies approach to heritage - Watson, Sheila; Barnes, Amy (Amy Jane); Bunning, Katy (Abingdon, Oxon ; New York, NY : Routledge, 2019)
"Heritage's revival as a respected academic subject has, in part, resulted from an increased awareness and understanding of indigenous rights and non-Western philosophies and practices, and a growing respect for the intangible. Heritage has thus focused on management, tourism and the traditionally 'heritage-minded' disciplines, such as archaeology and geography, social and cultural theory. Scholarly work in this area has been in support of identity and community cohesion, as well as championing new approaches to ethics and values. Widening the scope of international heritage studies by drawing on a range of disciplines as well as the best from established sources, A Museum Studies Approach to Heritage explores heritage through new areas of knowledge including emotion and affect, the politics of dissent, migration and intercultural and participatory dimensions of heritage. It includes writing not typically recognised as 'heritage' but which, nevertheless, adds something significant to heritage debates: what heritage is, what it can do, how it works and for whom. The book includes heritage perspectives from beyond the professional sphere, serving as a reminder that heritage is not just the concern of the academic, but is a deeply felt and keenly valued public and private practice. This blending of traditional topics and emerging trends, established theory and concepts from other disciplines offers readers international views of the past and future of this growing field. A Museum Studies Approach to Heritage is an introductory reader for postgraduate students of heritage studies, museum studies and everyone interested in how we conceptualise and use the past"--
Heritage contexts, past and present: Introduction / Amy Jane Barnes -- Heritage pasts and heritage presents / David Harvey -- Museum Studies and Heritage: Independent museums and the "heritage debate" in the UK / Anna Woodham -- People [extracts] / Alan Bennett -- The crisis of cultural authority / Tiffany Jenkins -- Editorials: History Workshop Journal / Editorial Collective/Raphael Samuel -- Hybrids / Raphael Samuel -- Understanding our encounters with heritage: the value of "historical consciousness" / Ceri Jones -- Weighing up intangible heritage: A view from Ise / Simon Richards -- From monument to cultural patrimony: The concepts and practices of heritage in Mexico / Cintia Velázquez Marroni -- We come from the land of the ice and snow: Icelandic heritage and its usage in present day society / Guðrún D. Whitehead -- Por la encendida calle antillana: Africanisms and Puerto Rican architecture / Arleen Pabón -- Iconoclash in the age of heritage [extracts] / Peter Probst -- Authenticity and tourism: Introduction / Sheila Watson -- Touring the Slave Route: Inaccurate Authenticities in Benin, West Africa / Timothy Landry -- Steampunking heritage: How Steampunk artists reinterpret museum collections / Jeanette Atkinson -- Why Fakes? / Mark Jones -- The work of art in the age of mechanical reproduction / Walter Benjamin -- After authenticity at an American heritage site / Eric Gable and Richard Handler -- Makeover for Mont-Saint-Michel / Alexander Stille -- Resonance and wonder / Stephen Greenblatt -- "Introduction" to In Search of Authenticity: The formation of folklore studies / Regina Bendix -- Emotions and materiality: Introduction / Sheila Watson -- Invoking affect / Clare Hemmings -- The Archaeology of Mind [extracts] / Jaak Panksepp and Lucy Biven -- "The trophies of their wars": Affect and encounter at the Canadian War Museum / Sara Matthews -- Huddled Masses Yearning to Buy Postcards: The politics of producing heritage at the Statue of Liberty-Ellis Island National Monument / Joanne Maddern -- The Holocaust and the Museum World in Britain: a study of ethnography / Tony Kushner -- Senses of place, senses of time and heritage / Gregory John Ashworth and Brian Graham -- Making heritage pay in the Rainbow Nation / Lynn Meskell -- The concept and its varieties / Anthony Smith -- Materiality Matters: Experiencing the displayed object / Sandra Dudley --Concepts of identity and difference / Kathryn Woodward -- Emotional engagement in heritage sites and museums: Ghosts of the past and imagination in the present / Sheila Watson -- The Third World / Jeremy Black -- Turkish Delight: Antonio Gala's La pasión turca as a Vision of Spain's Contested Islamic Heritage / Nicola Gilmour -- "The cliffs are not the cliffs": The cliffs of Dover and national identities in Britain, c.1750-c.1950 / Paul Readman -- Diversity and identity: Introduction / Katy Bunning -- Museums as intercultural spaces / Simona Bodo -- Gradients of alterity: museums and the negotiation of cultural difference in contemporary Norway / Marzia Varutti -- Museums in a global world: a conversation on museums, heritage, nation and diversity in a transnational age / Conal McCarthy, Rhiannon Mason, Christopher Whitehead, Jakob Ingemann Parby, André Cicalo, Philipp Schorch, Leslie Witz, Pablo Alonso Gonzalez, Naomi Roux, Eva Ambos and Ciraj Rassool -- Reflections on the Confluence Project: Assimilation, sustainability, and the perils of a shared heritage / Jon Daehnke -- Ethnic heritage for the nation: Debating "identity museums" on the National Mall / Katy Bunning -- Heritage interpretation and human rights: documenting diversity, expressing identity, or establishing universal principles? / Neil Silberman -- Un-placed heritage: Making identity through fashion / Malika Kraamer and Amy Jane Barnes -- Participatory heritage: Introduction / Katy Bunning -- Research on community heritage: Moving from collaborative research to participatory and co-designed research practice / Andrew Flinn and Anna Sexton -- Beyond the rhetoric: Negotiating the politics and realising the potential of community-driven heritage engagement / Corinne Perkin -- From representation to participation: Inclusive practices, co-curating and the voice of the protagonists in some Italian migration museums / Anna Chiara Cimoli -- Museums, trans youth and institutional change: Transforming heritage institutions through collaborative practice / Serena Iervolino -- Embrace the margins: Adventures in archaeology and homelessness / Rachael Kiddey and John Schofield -- Developing dialogue in co-produced exhibitions: Between rhetoric, intentions and realities / Nuala Morse, Morag Macpherson and Sophie Robinson -- Community engagement, curatorial practice and museum ethos in Alberta, Canada / Bryony Onciul -- Contested histories and heritage: Introduction / Sheila Watson -- Contested townscapes: the walled city as World Heritage / Oliver Creighton -- Reassembling Nuremberg, reassembling heritage / Sharon Macdonald -- Can there be a conciliatory heritage? / Erica Lehrer -- Palimpsest memoryscapes: Materializing and mediating war and peace in Sierra Leone / Paul Basu -- Representing the China Dream: A case study in revolutionary cultural heritage / Amy Jane Barnes -- Contested trans-national heritage: the demolition of Changi Prison, Singapore / Joan Beaumont -- The politics of community heritage: motivations, authority and control / Elizabeth Crooke -- "To Make the Dry Bones Live": Amédée Forestier's Glastonbury Lake Village / James E. Phillips -- "Introduction" to contested landscapes: movement, exile and place / Barbara Bender -- Sensuous (re)collections: The sight and taste of socialism at Grutas Statue Park, Lithuania / Gediminis Lankauskas .
Includes bibliographical references and index.
ARC
Parama
Keywords: Cultural property -- Protection; Museums